Rapid identification of A29L antibodies based on mRNA immunization and high-throughput single B cell sequencing to detect Monkeypox virus - Huisheng Sun; Yiqi Miao; Xingsheng Yang; Liang Guo; Qingyu Li; Jing Wang; Jinrong Long; Zhen Zhang; Jingqi Shi; Jian Li; Yiming Cao; Changxiao Yu; et al. (Emerging Microbes and Infections, 2024)
ABSTRACTWith the large number of atypical cases in the mpox outbreak, which was classified as a global health emergency by the World Health Organization (WHO) on 23 July 2022, rapid diagnosis of mpox and diseases with similar symptoms to mpox such as chickenpox and respiratory infectious diseases in the early stages of viral infection is key to controlling the spread of the outbreak. In this study, antibodies against the monkeypox virus A29L protein were efficiently and rapidly identified by combining rapid mRNA immunization with high-throughput sequencing of individual B cells. We obtained eight antibodies with a high affinity for A29L validated by ELISA, which were was used as the basis for developing an ultrasensitive fluorescent immunochromatographic assay based on multilayer quantum dot nanobeads (SiTQD-ICA). The SiTQD-ICA biosensor utilizing M53 and M78 antibodies showed high sensitivity and stability of detection: A29L was detected within 20 min, with a minimum detection limit of 5 pg/mL. A specificity test showed that the method was non-cross-reactive with chickenpox or common respiratory pathogens and can be used for early and rapid diagnosis of monkeypox virus infection by antigen detection. This antibody identification method can also be used for rapid acquisition of monoclonal antibodies in early outbreaks of other infectious diseases for various studies.